PENINGKATAN LITERASI DAN INKLUSI ZAKAT MELALUI PROGRAM “ZAKAT GOES TO SCHOOL” - Haura, Arie; Mandiri, Dewi Putri; Komariyah, Oom; Septi, Iti; Maulana, M.Firman; Haikal, Fiqi (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
This activity aims to provide literacy and as an effort to increase zakat inclusion. The activity can be implemented through cooperation between Inisistif Zakat Indonesia (IZI) and the Faculty of Islamic Economics and Business-Universitas Cendekia Abditama (FEBI-UCA). The activity successfully implemented in Indonesian Cendekia Madani and Ash Shibghoh Schools, Tangerang, Banten. The activities are received zakat payments at booths and seminars related to zakat jurisprudence. The acceptance of zakat fitrah, zakat maal, and alms at the booth went smoothly and the seminar participants were also enthusiastic in receiving the material.